Pengaruh Think Pair Share Berbasis Blended Learning Terhadap Hasil Belajar Matematika - Sugiyanti, Sugiyanti (Jurnal Kualita Pendidikan, 2024)
The Covid-19 pandemic has changed the learning system in Indonesia from face-to-face learning to distance learning. Such changes in the learning system need to be addressed by using a learning model that is in accordance with the distance learning system. Blended learning is a learning approach that combines face-to-face and online learning as an alternative to this change in the learning system. This study aims to determine the effect of the think pair share (TPS) model based on blended learning on students' mathematics learning outcomes. Quantitative research by comparing two learning models on students' mathematics learning outcomes. The research sample was from grade VI students of SD N Mrisen 1 in Demak Regency. The results of the study obtained that the TPS model based on blended learning had an effect of 71.9% on student learning outcomes. This shows that the blended learning approach to the TPS model significantly affects students' mathematics learning outcomes.